Literasi Digital Peserta Didik Berbasis Nilai-Nilai Hadis - Wildan, Labibul (INCARE, International Journal of Educational Resources, 2025)
This study aims to examine and analyze the concept of digital literacy among students based on Hadith values as a response to ethical and media behavior challenges in the digital age. The phenomenon of low internalization of values such as manners, honesty, and tabayyun in students' digital activities is the main issue behind this study. The research uses a qualitative approach with a library research method, which systematically examines nationally and internationally indexed journal articles, academic books, and relevant scientific documents published between 2020 and 2025. Data collection techniques were carried out through searching, selecting, and thematic analysis of literature sources discussing digital literacy, Islamic education, and Hadith values. The results of the study show several main themes, namely: (1) digital literacy as an ethical and valuable practice, (2) the relevance of Hadith values such as tabayyun, amanah, and adab in the digital space, and (3) the importance of integrating Hadith values in students' digital literacy learning. These findings contribute to strengthening the conceptual understanding of digital literacy in the perspective of Islamic education. This study concludes that Hadith-based digital literacy has the potential to become a normative and practical framework in shaping students' character, and recommends further empirical research to test its implementation in the context of formal education.